1996
DOI: 10.6028/nist.tn.1421
|View full text |Cite
|
Sign up to set email alerts
|

A national measurement system for radiometry, photometry, and pyrometry based upon absolute detectors

Abstract: Gaithersburg, MD USA 20899-0001 Advancements in the performance and ease of use of absolute photodetectors based upon electrical substitution principals offers the possibility of a simplified and more accurate way to transfer the fundamental radiometric, photometric, and pyrometric units from NIST to the U.S. technical establishment. The history of electrical substitution radiometers at NIST is briefly reviewed and the implementation of the latest generation absolute cryogenic radiometer is discussed. Procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…1 The optical power measurement is obtained through the measurement of electrical power. By knowing the amount of electric power fed into the system, incident optical power levels ranging from 1 μW to 1 mW can be determined.…”
Section: Cryogenic Radiometry As Primary Standardmentioning
confidence: 99%
“…1 The optical power measurement is obtained through the measurement of electrical power. By knowing the amount of electric power fed into the system, incident optical power levels ranging from 1 μW to 1 mW can be determined.…”
Section: Cryogenic Radiometry As Primary Standardmentioning
confidence: 99%
“…A physical model was developed to interpolate the responsivity of silicon trap detectors over the spectral range from 405 nm to 920 nm [24]. Outside of this spectral range, the detector responsivity scale was based on pyroelectric detector with a spectrally flat responsivity [21]. [17,24,26], and no interference problem with laser emission.…”
Section: 3mentioning
confidence: 99%
“…The measurement equation for the "substitution method with monitor" (Fig. 3.3 x-^x=^x-Gx-^bsx-^x-^x, (3.21) and = K,^^-"^= s^^• p^sx '^x "^x • (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) The ratio of these two signals is: Vis/NIR SCF using the 100 W quartz-halogen lamp and (b) UV SCF using the argon mini-arc as a source. The Optical Technology Division within NIST presently has two cryogenic radiometers that provide the basis for the spectral radiant power responsivity scale: the NIST-designed POWR (Figure 5.2), and the L-1 ACR [23] (Figure 5.3 intercomparison between POWR and the L-1 ACR showed that these two standards agreed to within 0.02 %, which is within their combined uncertainties as shown in Figure 5.4 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Outside of this spectral range, the detector responsivity scale was based on pyroelectric detector with a spectrally flat responsivity [13] . While the pyroelectric detector had a spectrally flat responsivity, its absolute responsivity value was low.…”
Section: Calibration Of Transfer Standards With a Cryogenic Radiometermentioning
confidence: 99%